A catalyst for low-pressure olefin polymerization and its preparation method and application

By using COF-based ZR metal catalysts ZR-TTDA catalytic hydrin aggregation under low pressure, the problem of decreased activity and impurity introduction of traditional catalysts in low pressure under low pressure, and achieve efficient and stable catalytic effects.

CN116640242BActive Publication Date: 2025-01-28ANQING NORMAL UNIV
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202310451795.7
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2023-04-24
Publication Date
2025-01-28
Estimated Expiration
2043-04-24

AI Technical Summary

Technical Problem

The prior art is difficult to effectively catalyze olefin polymerization under low pressure, and the catalytic activity of conventional catalysts decreases and introduces impurities when homogeneously fixed.

Method used

ZR-TTDA, a ZR metal catalyst based on covalent-based organic framework (COF). Phenyldererdehyde reacts with ZRCL4, and uses frozen-sealing management method to improve yield and thermal stability.

Benefits of technology

At low pressure, a strong catalytic ethylene aggregation activity is shown, with high yield and good thermal stability. It avoids the introduction of impurities and has application prospects.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN116640242B_ABST
    Figure CN116640242B_ABST
Patent Text Reader

Abstract

The invention discloses a catalyst for low-pressure olefin polymerization, a preparation method and an application thereof, and belongs to the technical field of organic porous crystalline polymers and COF materials thereof. The preparation method comprises the following steps: (1) preparing an active sample TdDa: mixing 2,4,6-tris(4-aminophenyl)-1,3,5-triazine, 2,5-dihydroxyterephthalaldehyde, mesitylene and ethanol to obtain an active sample TtDa; (2) preparing a catalyst Zr-TtDa: placing TtDa and ZrCl4 in a reaction vessel, injecting tetrahydrofuran under vacuum, heating and stirring, centrifuging, and drying to obtain dry Zr-TtDa. Beneficial effect: The catalyst of the invention is a Zr metal catalyst based on COF, which is the first to introduce a molecular Zr catalyst into the COF pores to construct a multiphase olefin polymerization catalyst. The synthesis method is simple, the pores are methylated, the raw materials are easily available, and the crystalline material exhibits high porosity and catalytic activity. The results of ethylene polymerization test studies show that it can be used as an olefin polymerization in the field of multiphase catalysis.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of organic porous crystalline polymer and olefin polymerization catalysis, and specifically relates to a preparation method and application of a low-pressure olefin polymerization catalyst. Background Art

[0002] Covalent organic frameworks (COFs) with regular channel structures and flexible porosity have been widely studied due to their excellent performance in gas storage and separation, removal of heavy metals and toxic organic pollutants, chemical sensing and heterogeneous catalysis. It is worth noting that COFs with specific structures and functions can be designed and synthesized according to actual experimental needs, and the shape and size of their nanochannels can be easily adjusted by changing the type and size of monomers to improve their catalytic performance. Therefore, the application of COFs in the field of heterogeneous catalysis is very promising.

[0003] Single-site olefin polymerization catalysts, such as metallocene and non-metallocene catalysts, have some advantages over traditional Ziegler-Natta catalysts. However, single-site catalysts usually need to be fixed on a suitable support, such as silica or magnesium chloride, for industrial application. Homogeneous molecular catalysts are generally fixed on a support with a random structure, which leads to a huge decrease in their catalytic activity and loses some of the advantages of single-site catalysts, while also introducing additional impurities into the polymer products.

[0004] The metal active sites in the metallized COF (MCOF) catalyst are evenly distributed and have a confined environment with one-dimensional macropores, which indicates that it has the advantages of both homogeneous single-active site catalysts and heterogeneous supported catalysts, so that MCOFs can exhibit excellent performance in ethylene polymerization.

[0005] The Chinese patent application document with publication number CN107433205A discloses a covalent organic framework-supported cobalt catalyst and its preparation and application, and specifically discloses that the covalent organic framework (COFs) material supports metal cobalt for catalyzing carbon dioxide and epoxy compounds to synthesize cyclic carbonate compounds. The structural unit of the material contains a cobalt-porphyrin complex, which can be used to catalyze the reaction between carbon dioxide and epoxy compounds. In addition, COFs has a large specific surface area and an open pore structure, which can enhance the adsorption capacity of carbon dioxide. Therefore, the material can simultaneously achieve adsorption and catalytic conversion of carbon dioxide gas to generate cyclic carbonates under normal temperature and pressure conditions. The reaction substrate types can be expanded, the reaction yield is high, the catalyst can be recycled, the operation is simple, and the product added value is high. However, the patent does not involve properties related to ethylene polymerization and low-pressure catalytic ethylene polymerization. Summary of the invention

[0006] The technical problem to be solved by the present invention is how to provide a catalyst for low-pressure olefin polymerization.

[0007] The present invention solves the above technical problems through the following technical means:

[0008] The Zr metal catalyst based on COF of the present invention, namely Zr-TtDa, wherein Da is 2,5-dihydroxyterephthalaldehyde, and its structural formula is Tt is 2,4,6-tris(4-aminophenyl)-1,3,5-triazine, and its structural formula is The metal source is ZrCl4. Da and Tt are synthesized, and other reagents are commercially available.

[0009] The first aspect of the present invention provides a method for preparing a catalyst for low-pressure olefin polymerization, comprising the following steps:

[0010] (1) Preparation of active sample TtDa:

[0011] a. 2,4,6-tris(4-aminophenyl)-1,3,5-triazine (Tt), 2,5-dihydroxyterephthalaldehyde (Da), mesitylene and 1-butanol were mixed, ultrasonically treated, and then an acetic acid aqueous solution was added. The mixture was then degassed by freeze-pump-thaw cycles, the reaction mixture was sealed, cooled to room temperature, vacuum filtered, and washed to obtain a wet sample.

[0012] b. The wet sample is transferred to an extractor, washed with an organic solvent, and then washed with liquid carbon dioxide, and then heated to make the carbon dioxide reach a supercritical state, and slowly vented to ambient pressure; and then vacuumed under heating to obtain an active sample TtDa;

[0013] (2) Preparation of catalyst Zr-TtDa:

[0014] The active sample TtDa and ZrCl4 obtained in step (1) are placed in a reaction container, tetrahydrofuran (THF) is injected under vacuum, heated and stirred, centrifuged, and dried to obtain dry Zr-TtDa.

[0015] Beneficial effects: The present invention first reacts 2,4,6-tris(4-aminophenyl)-1,3,5-triazine and 2,5-dihydroxyterephthalaldehyde to prepare an active sample TtDa, and then reacts with ZrCl4 to obtain a COF-based Zr metal catalyst Zr-TtDa, which is prepared by a freezing-sealing tube method, has a high yield, high thermal stability, and exhibits strong catalytic ethylene polymerization activity under low pressure, and is expected to be applied in the olefin field.

[0016] Preferably, the molar ratio of Tt to Da in step a is 1-3:2-4.

[0017] Preferably, the molar ratio of Tt to Da in step a is 2:3.

[0018] Preferably, the ultrasonic treatment time in step a is 8-15 min.

[0019] Preferably, the reaction temperature in step a is 100-140° C., and the reaction time is 2-5 days.

[0020] Preferably, the organic solvent in step b is dioxane and tetrahydrofuran.

[0021] Preferably, the vacuuming under heating in step b is specifically: vacuuming at a speed of 0.1-0.2 MPa / min at 100-140° C. for 10-14 hours.

[0022] Preferably, in step (2), the mass ratio of TtDa to ZrCl4 is 3-5:0.5-1.5.

[0023] Preferably, in step (2), the mass ratio of TtDa to ZrCl4 is 4:1.

[0024] Preferably, the heating temperature in step (2) is 60-80°C.

[0025] Preferably, the stirring time in step (2) is 10-14 hours.

[0026] Preferably, the drying in step (2) is vacuum drying at 30-50° C. for 10-14 h.

[0027] The second aspect of the present invention provides a catalyst for low-pressure olefin polymerization prepared by the above method.

[0028] The third aspect of the present invention provides an application of a catalyst for low-pressure olefin polymerization prepared by the above method in olefin polymerization.

[0029] The advantages of the present invention are:

[0030] 1. The present invention first reacts 2,4,6-tris(4-aminophenyl)-1,3,5-triazine and 2,5-dihydroxyterephthalaldehyde to prepare an active sample TtDa, and then reacts with ZrCl4 to obtain a COF-based Zr metal catalyst Zr-TtDa, which is prepared by a freezing-sealing tube method, has a high yield, high thermal stability, and exhibits strong catalytic ethylene polymerization activity under low pressure, and is expected to be applied in the olefin field.

[0031] 2. The Zr metal catalyst based on COF of the present invention is the first to introduce molecular Zr catalyst into COF pores to construct a multiphase olefin polymerization catalyst.

[0032] 3. The catalyst of the present invention is a molecular Zr catalyst supported by a covalent organic framework. Its synthesis method is simple, the synthesis yield is high, the raw materials are easily available, and its crystalline material exhibits high thermal stability and strong catalytic activity. The results of ethylene polymerization test show that it can be used as olefin polymerization in the field of chemical technology. BRIEF DESCRIPTION OF THE DRAWINGS

[0033] Figure 1 is a (100) crystal plane image of the catalyst for low-pressure olefin polymerization prepared in Example 1 of the present invention;

[0034] Figure 2 is a powder diffraction pattern of the catalyst for low-pressure olefin polymerization prepared in Example 1 of the present invention;

[0035] Figure 3 1 are infrared spectra of the catalyst for low-pressure olefin polymerization prepared in Example 1 of the present invention, wherein (a) is the FTIR spectrum of TtDa, and (b) is the FTIR spectrum of Zr-TtDa;

[0036] Figure 4 1 is an X-ray photoelectron spectrum of the catalyst for low-pressure olefin polymerization prepared in Example 1 of the present invention, wherein (a) is an X-ray photoelectron spectrum of TtDa, (b) is a Zr 3d XPS spectrum of Zr-TtDa, (c) is a comparison of the O1s peaks of the phenolic hydroxyl groups in TtDa and Zr-TtDa, and (d) is a comparison of the N1s peaks on the imine bonds in TtDa and Zr-TtDa;

[0037] Figure 5 are scanning electron microscope images of the catalyst for low-pressure olefin polymerization prepared in Example 1 of the present invention, wherein (a) is a scanning electron microscope image of TtDa, and (b) is a scanning electron microscope image of Zr-TtDa;

[0038] Figure 6 It is the N2 adsorption / desorption spectrum of the catalyst for low-pressure olefin polymerization prepared in Example 1 of the present invention, wherein (a) is a porosity comparison diagram of TtDa and Zr-TtDa, and (b) is a pore size distribution diagram of Zr-TtDa and its parent COF. DETAILED DESCRIPTION

[0039] In order to make the purpose, technical solution and advantages of the embodiments of the present invention clearer, the technical solution in the embodiments of the present invention will be clearly and completely described in combination with the embodiments of the present invention. Obviously, the described embodiments are part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0040] The invention discloses a Zr metal catalyst based on COF, namely Zr-TtDa, wherein Da is 2,5-dihydroxyterephthalaldehyde, Tt is 2,4,6-tris(4-aminophenyl)-1,3,5-triazine, and the metal source is ZrCl4.

[0041] Embodiment 1:

[0042] A method for preparing a catalyst for low-pressure olefin polymerization comprises the following steps:

[0043] (1) Preparation of active sample TtDa:

[0044] a. Tt (14.2 mg, 0.04 mmol), Da (10 mg, 0.06 mmol), mesitylene (1 mL) and 1-butanol (1 mL) were placed in a 15 mL Schlenk tube (OD 26 × L 70 mm) and mixed. After ultrasonic treatment for 10 minutes, 6 M acetic acid aqueous solution (200 uL) was slowly added, and then degassed by freeze-pump-thaw cycle. The tube was sealed and reacted at 120 ° C for 3 days; after cooling to room temperature, the yellow product was collected by vacuum filtration and washed with acetone 3 times to obtain a wet sample;

[0045] b. The wet sample is then transferred to a Soxhlet extractor, first washed with dioxane for 24 hours, then washed with tetrahydrofuran for 24 hours to thoroughly clean the sample, and then washed with liquid carbon dioxide 5 times, and then the system is heated to 45°C to make the carbon dioxide reach a supercritical state and slowly vented to ambient pressure; then the product is vacuumed at 120°C at a speed of 0.15 MPa / min for 12 hours to obtain the active sample TtDa.

[0046] (2) Preparation of catalyst Zr-TtDa:

[0047] Weigh 20.0 mg TtDa and 5.0 mg ZrCl4 respectively into a 50 mL two-necked flask, inject 2.0 mL THF under vacuum, and slowly stir at 66 °C for 12 h; centrifuge the obtained black solid from the suspension, wash with THF 4-5 times, and vacuum dry at 40 °C for 12 h to obtain dry Zr-TtDa.

[0048] The catalyst Zr-TtDa prepared in this example: In the XRD spectrum, the strong peaks at 3.10° correspond to the (100) plane of TtDa (such as Figure 1 ), while the weak peaks at 5.22°, 5.96°, and 7.74° correspond to the (110), (200), and (210) crystal planes, respectively. No additional signal peaks were observed in the XRD pattern of Zr-TtDa, indicating that the crystal structure was maintained after the addition of Zr (as shown in Figure 2The instrument used was an X-ray powder diffractometer (model D8 Advance, Bruker).

[0049] The characteristic infrared absorption peak of the catalyst Zr-TtDa is (KBr, cm -1 ): In the Fourier transform infrared spectrum (FTIR) of TtDa, the ─NH2 of Tt (3312~3406cm -1 ) and Da-CHO (1704cm -1 ) disappeared, and the typical characteristic peak signal at 1619cm -1 New imine bond (─C=N─) characteristic peaks appeared (such as Figure 3 (a) shows that TtDa was successfully prepared. It is worth noting that the FTIR spectrum of Zr-TtDa showed 469 cm -1 The stretching vibration bands indicate the formation of Zr-O bonds, i.e., Zr 4+ Coordinate with the O atom on the phenolic hydroxyl group (such as Figure 3 (b)). The instrument used is a FT-IR instrument (model VECTOR-22, Bruker).

[0050] Photoelectron spectroscopy analysis of the above catalyst Zr-TtDa: The X-ray photoelectron spectrum (XPS) of TtDa consists of three groups of element peaks: C, N and O, while new Zr and Cl peaks were detected in Zr-TtDa (such as Figure 4 The Zr 3dXPS spectrum of Zr-TtDa provides the binding energy peaks of Zr 3d5 / 2 and Zr 3d3 / 2 at 182.88 eV and 185.35 eV, respectively (as shown in Figure 2A). Figure 4 The O1s peak of the phenolic hydroxyl group in Zr-TtDa (532.78 eV) shows a slight downward shift compared with that of TtDa (532.79 eV), which is caused by the coordination of the O atom on the phenolic hydroxyl group with Zr (as shown in Fig. Figure 4 (c)). The N1s peak in Zr-TtDa (399.00 eV) shows a slight upshift compared with TtDa (398.90 eV), which is attributed to the coordination effect of the N atom with the imine bond of Zr (e.g. Figure 4 (d)). These results indicate that the N atom on the imine bond and the O atom on the phenolic hydroxyl group coordinate with Zr, while the other coordination sites around Zr are occupied by three Cl- and one tetrahydrofuran molecule to achieve charge balance. The instrument used is an XPS instrument (model K-alpha, ThermoFisherScientific).

[0051] Surface morphology analysis of the above catalyst Zr-TtDa: Scanning electron microscopy (SEM) showed that Zr-TtDa and TtDa were mainly in the form of flakes (e.g. Figure 5 The instrument used was a SEM instrument (model SMART APEXⅡ, Bruker AXS).

[0052] The above catalyst Zr-TtDa was tested for N2 adsorption at 77K: The porosity of TtDa and Zr-TtDa was measured by N2 adsorption / desorption at 77K (e.g. Figure 6 The Brunauer-Emmett-Teller (BET) surface areas of TtDa are 873.83 m 2 g -1 This is almost Zr-TtDa (460.01m 2 g -1 ) is twice the surface area, which is due to the introduction of Zr ions in COFs. The pore size distribution shows that the pores of Zr-TtDa and its parent COF are concentrated in (like Figure 6 (b)). The instrument used is a BET instrument (model ASAP 2460 Micromeritics).

[0053] The Zr metal catalyst based on COF, namely Zr-TtDa, was further characterized as follows:

[0054] Study on the performance of ethylene polymerization based on COF Zr metal catalyst (Zr-TtDa):

[0055] The results of Zr-TtDa for low-pressure polymerization of ethylene are shown in Table 1. The catalytic activity and weight-average molecular weight increase with increasing ethylene pressure (as shown in Examples 1 to 3 in Table 1 below). In order to study the effect of the amount of cocatalyst methylaluminoxane (MAO) on the catalytic performance of these Zr-TtDa / MAO systems, we conducted ethylene polymerization experiments with different MAO amounts and found that the catalytic activity increased with increasing MAO amounts (as shown in Examples 4 to 6 in Table 1 below). This may be due to more metal sites being activated as catalytic sites and faster alkyl chain removal rates. At Al / Zr = 2000 mol / mol, the catalytic activity reached a maximum value of 4.25×10 4 g PE mol Zr -1 ·h -1 .

[0056] Table 1 Ethylene polymerization using Zr-TtDa

[0057]

[0058] a Activity = mass of ethylene consumed per mole of exchange metal per hour (g PE ·mol Zr -1 ·h -1 ). b The weight average molecular weight (M) was determined by high temperature gel permeation chromatography. w ), number average molecular weight (M n ) and polydispersity index (D). Melting point (T) was determined by differential scanning calorimetry (DSC). M ). d Al / Zr=1000 mol / mol. e Al / Zr=1500 mol / mol. f Al / Zr=2000mol / mol.

[0059] Embodiment 2:

[0060] A method for preparing a catalyst for low-pressure olefin polymerization comprises the following steps:

[0061] (1) Preparation of active sample TtDa:

[0062] a. Tt (0.02 mmol), Da (0.06 mmol), mesitylene (1 mL) and 1-butanol (1 mL) were placed in a 15 mL Schlenk tube (OD 26 × L 70 mm) and mixed. After ultrasonic treatment for 8 minutes, 6 M acetic acid aqueous solution (200 uL) was slowly added, and then degassed by freeze-pump-thaw cycle. The tube was sealed and reacted at 100 ° C for 5 days; after cooling to room temperature, the yellow product was collected by vacuum filtration and washed with acetone 3 times to obtain a wet sample;

[0063] b. The wet sample is then transferred to a Soxhlet extractor, first washed with dioxane for 24 hours, then washed with tetrahydrofuran for 24 hours to thoroughly clean the sample, and then washed with liquid carbon dioxide 5 times, and then the system is heated to 45°C to make the carbon dioxide reach a supercritical state and slowly vented to ambient pressure; the product is then vacuumed at 100°C at a speed of 0.1 MPa / min for 14 hours to obtain the active sample TtDa.

[0064] (2) Preparation of catalyst Zr-TtDa:

[0065] Weigh 15.0 mg TtDa and 2.5 mg ZrCl4 respectively into a 50 mL two-necked flask, inject 2.0 mL THF under vacuum, and stir slowly at 60°C for 14 h; centrifuge the obtained black solid from the suspension, wash with THF 4-5 times, and vacuum dry at 30°C for 14 h to obtain dry Zr-TtDa.

[0066] Embodiment 3:

[0067] A method for preparing a catalyst for low-pressure olefin polymerization comprises the following steps:

[0068] (1) Preparation of active sample TtDa:

[0069] a. Tt (0.06 mmol), Da (0.08 mmol), mesitylene (1 mL) and 1-butanol (1 mL) were placed in a 15 mL Schlenk tube (OD 26 × L 70 mm) and mixed. After ultrasonic treatment for 15 minutes, 6 M acetic acid aqueous solution (200 uL) was slowly added, and then degassed by freeze-pump-thaw cycle. The tube was sealed and reacted at 140 ° C for 2 days; after cooling to room temperature, the yellow product was collected by vacuum filtration and washed with acetone 3 times to obtain a wet sample;

[0070] b. The wet sample is then transferred to a Soxhlet extractor, first washed with dioxane for 24 hours, then washed with tetrahydrofuran for 24 hours to thoroughly clean the sample, and then washed with liquid carbon dioxide 5 times, and then the system is heated to 45°C to make the carbon dioxide reach a supercritical state and slowly vented to ambient pressure; the product is then vacuumed at 140°C at a speed of 0.2 MPa / min for 10 hours to obtain the active sample TtDa.

[0071] (2) Preparation of catalyst Zr-TtDa:

[0072] Weigh 25.0 mg TtDa and 7.5 mg ZrCl4 respectively into a 50 mL two-necked flask, inject 2.0 mL THF under vacuum, and slowly stir at 80°C for 10 h; centrifuge the obtained black solid from the suspension, wash with THF 4-5 times, and vacuum dry at 50°C for 10 h to obtain dry Zr-TtDa.

[0073] The above embodiments are only used to illustrate the technical solutions of the present invention, rather than to limit the same. Although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art should understand that the technical solutions described in the aforementioned embodiments may still be modified, or some of the technical features may be replaced by equivalents. However, these modifications or replacements do not deviate the essence of the corresponding technical solutions from the spirit and scope of the technical solutions of the embodiments of the present invention.

Claims

1. A method for preparing a catalyst for low-pressure olefin polymerization, characterized in that: The following steps are involved: (1) Preparation of active sample TtDa: a. 2,4,6-tris(4-aminophenyl)-1,3,5-triazine, 2,5-dihydroxyterephthalaldehyde, mesitylene and 1-butanol were mixed, ultrasonically treated, and then an aqueous acetic acid solution was added, followed by degassing by freeze-pump-thaw cycle, the reaction was sealed, cooled to room temperature, vacuum filtered, and washed to obtain a wet sample; the molar ratio of 2,4,6-tris(4-aminophenyl)-1,3,5-triazine to 2,5-dihydroxyterephthalaldehyde was 1-3:2-4; b. The wet sample is transferred to an extractor, washed with an organic solvent, and then washed with liquid carbon dioxide, and then heated to make the carbon dioxide reach a supercritical state, and slowly vented to ambient pressure; and then vacuumed under heating to obtain an active sample TtDa; (2) Preparation of catalyst Zr-TtDa: The active sample TtDa and ZrCl4 obtained in step (1) are placed in a reaction container, tetrahydrofuran (THF) is injected under vacuum, heated and stirred, centrifuged, and dried to obtain dry Zr-TtDa; the mass ratio of TtDa to ZrCl4 is 3-5:0.5-1.

5.

2. The method for preparing a catalyst for low-pressure olefin polymerization according to claim 1, characterized in that: In the step a, the molar ratio of 2,4,6-tris(4-aminophenyl)-1,3,5-triazine to 2,5-dihydroxyterephthalaldehyde is 2:

3.

3. The method for preparing a catalyst for low-pressure olefin polymerization according to claim 1 or 2, characterized in that: The ultrasonic treatment time in step a is 8-15 minutes; the reaction temperature in step a is 100-140° C., and the reaction time is 2-5 days.

4. The method for preparing a catalyst for low-pressure olefin polymerization according to claim 3, characterized in that: The organic solvent in step b is dioxane and tetrahydrofuran.

5. The method for preparing a catalyst for low-pressure olefin polymerization according to claim 4, characterized in that: The vacuuming under heating in step b is specifically: vacuuming at a speed of 0.1-0.2 MPa / min for 10-14 hours at 100-140°C.

6. The method for preparing a catalyst for low-pressure olefin polymerization according to claim 1, characterized in that: The mass ratio of TtDa to ZrCl4 in step (2) is 4:

1.

7. The method for preparing a catalyst for low-pressure olefin polymerization according to claim 1, characterized in that: The heating temperature in step (2) is 60-80° C.; the stirring time in step (2) is 10-14 h.

8. The method for preparing a catalyst for low-pressure olefin polymerization according to claim 1, characterized in that: The drying in step (2) is specifically performed by vacuum drying at 30-50° C. for 10-14 hours.

9. A catalyst prepared by the preparation method according to any one of claims 1 to 8.

10. Use of the catalyst prepared by the preparation method according to any one of claims 1 to 8 in olefin polymerization.

Citation Information

Patent Citations

  • Covalent organic frameworks-supported cobalt catalyst and preparation and application thereof

    CN107433205A

  • Covalent organic framework and catalyst, preparation methods therefor, and applications thereof

    WO2022133843A1